(untitled) (New York, 2012)
Subject Areas/Keywords: assessments, decoding, elementary, English language learners, fluency, literacy instruction, oral reading, primary grades, prosody, reading comprehension, reading expressiveness, reading methods, secondary, struggling readers Description: This accessible guide brings together well-known authorities to examine what reading fluency is and how it can best be taught. Teachers get a clear, practical roadmap for navigating the often confusing terrain of this crucial aspect of balanced literacy instruction. Innovative approaches to instruction and assessment are described and illustrated with vivid examples from K-12 classrooms. The book debunks common misconceptions about fluency and clarifies its key role in comprehension. Effective practices are presented for developing fluency in specific populations, including English language learners, adolescents, and struggling readers
Keywords: Reading,Đọc hiểu; Remedial teaching.,Giảng dạy khắc phục hậu quả